(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The purpose of this study is to determine the effect of self efficacy, self esteem and empowerment on employee job satisfaction at PT. BPR Bank Kertiawan Denpasar partially and simultaneously. The sample in this study was used 35 respondents and using the saturated sampling method. Instrument testing is carried out by validity and reliability test and using multiple linear regression analysis techniques in hyphothesis test. This study obtained self efficacy partially has a positive and significant effect on employee job satisfaction. Self esteem partially has a positive and significant effect on employee jonb satisfaction. Empowerment has a positive effect on employee job satisfaction. Self efficacy, self esteem and empowerment simultaneously have a positive and significant effect on employee job satisfaction at PT. BPR Bank Kertiawan Denpasar. Suggestions that can given include leaders should give apprestiation for employee work performance, empower the employee potential and give attention to comfort and all supporting aspects to increase employee job satisfaction to achieve company goals.